Gender Differences in Risk-Taking: Evidence from Professional Basketball - René Böheim; Christoph Freudenthaler; Mario Lackner (Institute for the Study of Labor (IZA), 2016)
We analyze gender differences in risk-taking in high-pressure situations. Using novel data from professional athletes (NBA and WNBA), we find that male teams increase their risk-taking towards the end of matches when a successful risky strategy could secure winning the match. Female teams, in contrast, reduce their risk-taking in these situations. The less time left in a match, the larger is the gap. When the costs of an unsuccessful risky strategy are very large (losing the tournament), we find no increase in risk-taking for male teams.
Keywords: D81; J16; L83; 330; risk-taking; gender differences; tournament incentives